INVESTIGATION THE EFFECTS OF COMBINED PLYOMETRICS WITH BASKETBALL TRAINING ON SOME BIOMOTORICAL PERFORMANCE - Özhan BAVLI (Pamukkale University, 2012)
The purpose of this study was to investigate the effects combined six weeks plyometric traning with basketball training on one repetition maksimum squat, 30 vertical jump and 30 meter sprint perfromance. Twenty-four licensed active male basketball players joined in to study as a volunteer. The average age of the players was 20,7±2,6 years. Criteria of the selection were, subjects should have no history of any major injury, minimum two years licenced and could not be involved formal weight training for duration of the study. An informed consent form was read and signed by players beforeparticipation. Players were randomly assigned to either plyometric group (n=12) and control group (n=12). Plyometric group did 30 minutes plyometric exercises after basketball training but control group did not. One repetition maximum squat, 30 meter sprint and vertical jump performance evaluated before and after the training season. Data analyzed by "Wlcoxon Signed Ranks Test" for pretest-posttest differences and "Mann Whitney U-Test" for dfferences between groups. Results were accepted significant at p<0,05 level. Analyze showed that pretest-postest values of groups were significantly different (p<0.05) also there was significantly difference between groups of biomotorical features (p<0.05). Plyometric group achieved a statistically greater improvement (p<0,05) than the control group in one repetition maximum squat, 30 meter sprint and vertical jump performance. These findings suggest that the addition of plyometric training of the in season basketball training may be more benefical than the training alone for enhancing motorical features.